Dynamic Tensile Response of Seawater Coral Aggregate Concrete (SCAC) in Saturated State: Experimental and Numerical Simulation Study - Rui Li; Chaomin Mu; Yulin Qin; Hui Zhou; Quanmin Xie (Buildings)
Seawater Coral Aggregate Concrete (SCAC), made using coral aggregates from marine environments, is gaining attention as a promising material for marine and coastal engineering applications. This study investigates the dynamic tensile behavior of SCAC under both dry and saturated conditions, with an emphasis on the effects of free water on its mechanical properties. The dynamic Brazilian splitting (DBS) tests were conducted to evaluate the dynamic tensile strength, strain rate sensitivity, failure modes, and fracture morphology of SCAC specimens. The results show that saturated SCAC specimens exhibit a reduction in dynamic tensile strength compared to dry specimens, with this difference becoming more pronounced at higher strain rates. The maximum reduction can be observed to be 17.87%. Additionally, saturated SCAC specimens demonstrate greater strain rate sensitivity than dry specimens, which highlights the significant influence of moisture on the material’s mechanical behavior. The failure modes of SCAC were found to be less severe under saturated conditions, suggesting that moisture suppresses crack propagation to some extent, thereby reducing brittleness. Numerical simulations based on the finite element analysis were conducted to simulate the dynamic tensile response; the comparison of numerical and experimental data indicates that adjusting material model parameters effectively simulates the behavior of saturated SCAC.